FAM96A is a novel pro‐apoptotic tumor suppressor in gastrointestinal stromal tumors. Issue 6 (12th March 2015) - Schwamb, Bettina; Pick, Robert; Fernández, Sara Beatriz Mateus; Völp, Kirsten; Heering, Jan; Dötsch, Volker; Bösser, Susanne; Jung, Jennifer; Beinoraviciute‐Kellner, Rasa; Wesely, Josephine; Zörnig, Inka; Hammerschmidt, Matthias; et al.
<x xml:space="preserve">Abstract</x> The ability to escape apoptosis is a hallmark of cancer‐initiating cells and a key factor of resistance to oncolytic therapy. Here, we identify FAM96A as a ubiquitous, evolutionarily conserved apoptosome‐activating protein and investigate its potential pro‐apoptotic tumor suppressor function in gastrointestinal stromal tumors (GISTs). Interaction between FAM96A and apoptotic peptidase activating factor 1 (APAF1) was identified in yeast two‐hybrid screen and further studied by deletion mutants, glutathione‐S‐transferase pull‐down, co‐immunoprecipitation and immunofluorescence. Effects of FAM96A overexpression and knock‐down on apoptosis sensitivity were examined in cancer cells and zebrafish embryos. Expression of FAM96A in GISTs and histogenetically related cells including interstitial cells of Cajal (ICCs), "fibroblast‐like cells" (FLCs) and ICC stem cells (ICC‐SCs) was investigated by Northern blotting, reverse transcription—polymerase chain reaction, immunohistochemistry and Western immunoblotting. Tumorigenicity of GIST cells and transformed murine ICC‐SCs stably transduced to re‐express FAM96A was studied by xeno‐ and allografting into immunocompromised mice. FAM96A was found to bind APAF1 and to enhance the induction of mitochondrial apoptosis. FAM96A protein or mRNA was dramatically reduced or lost in 106 of 108 GIST samples representing three independent patient cohorts. Whereas ICCs, ICC‐SCs and FLCs, the presumed normal counterparts of GIST, were found to robustly express FAM96A protein and mRNA, FAM96A expression was much reduced in tumorigenic ICC‐SCs. Re‐expression of FAM96A in GIST cells and transformed ICC‐SCs increased apoptosis sensitivity and diminished tumorigenicity. Our data suggest FAM96A is a novel pro‐apoptotic tumor suppressor that is lost during GIST tumorigenesis.